A Methodology for Measuring the Heat Release Efficiency in Bubbling Fluidised Bed Combustors - Müller, Dominik; Plankenbühler, Thomas; Karl, Jürgen (Energies, 2020)
Differences in the densities of bed material and-especially biogenic-solid fuels prevent an ideal mixture within bubbling fluidised bed (BFB) combustors. So, the presence of fuel particles is usually observed mainly near the surface of the fluidised bed. During their thermal conversion, this leads to a release of unburnt pyrolysis products to the freeboard of the combustion chamber. Within the further oxidation, these species will not transfer their heat-of-reaction to the inert bed material in the way of a convective heat transfer, but rather increase the gas phase temperature providing probably some additional radiative heat transfer to the dense bed. In this case, the so-called heat release efficiency to the fluidised bed, being the ratio of transferred heat to the fuel input, will be reduced. This paper presents a methodology to quantify this heat release efficiency with lab-scale experiments and the observed effects of common operating parameters like bed temperature, fluidisation ratio and fuel-to-air ratio. Experimental results show that the air-to-fuel ratio dominates the heat release efficiency, while bed temperature and fluidisation ratio have minor influences.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bubbling fluidised bed; Combustion; Heat release efficiency